A mild and sequentially Pd/Cu-catalyzed domino synthesis of acidochromic Indolo[3, 2-a]carbazoles – Free bases of apocyanine dyes. (February 2020) - Niesobski, Patrik; Nau, Jennifer; May, Lars; Moubsit, Alae-Eddine; Müller, Thomas J.J.
Abstract: A sequentially Pd(II)/Cu(II)-catalyzed dimerization of indoles with subsequent oxidative cycloaromatization with alkynes give rise to the formation of strongly violet to blue solution and solid state emissive indolo[3, 2- a ]carbazoles in a domino fashion under mild conditions and in moderate to good yields. Upon protonation the absorption bands are significantly red-shifted with concomitant quenching of the fluorescence. The site of protonation was scrutinized by NMR studies of the protonated species and confirmed by DFT calculations. The obtained chromophores of the acidochromicity of the title compounds are rarely described apocyanine dyes. The relevant absorption bands can be unambiguously assigned by TDDFT calculations. Graphical abstract: Image 1 Highlights: The urgency and relevance of our contribution for a broad readership of organic, dye and materials chemists is justified by the following aspects: Our general approach is the concept of modular one-pot syntheses of functional dyes, predominantly fluorophores. Indolo[3, 2- a ]carbazoles are accessible by a Pd/Cu-catalyzed oxidative four-fold CH-activation that proceeds in a pseudo-threecomponent domino reaction. During our methodological studies we not only noticed that the title compounds are intensively violet to blue emissive in solution and in the solid state, but also acidochromic, i.e. a significant red shift of the absorption bands with concomitant fluorescence quenching . By comprehensive NMR studies the site of protonation as assessed, showing that the protonated species falls into the rarely occurring class of apocyanines. The site of protonation was additionally corroborated by DFT calculations on various conceivable isomers. The isosbestic points in the protonated absorption spectra as well as the static fluorescence quenching (Stern-Vollmer plot) furthermore allows determining the p Ka of conjugated acids of the title compounds, i.e. apocyanines. The elucidation of the electronic structure by DFT and TD DFT calculations using the PBEh1PBE functional reveals that the longest wavelength chromogenic absorption band can be indeed assigned to dominant cyanine like HOMO-LUMO transitions .